Nanoencapsulation of DMSA monoester for better therapeutic efficacy of the chelating agent against arsenic toxicity. (March 2014) - Yadav, Abhishek; Mathur, Rashi; Samim, Mohammed; Lomash, Vinay; Kushwaha, Pramod; Pathak, Uma; Babbar, Anil Kumar; Singh Flora, Swaran Jeet; Mishra, Anil Kumar; Kaushik, Mahabir Parshad
Aims: Exposure to toxic metals remains a widespread occupational and environmental problem in world. Chelation therapy is a mainstream treatment used to treat heavy metal poisoning. This paper describes the synthesis, characterization and therapeutic evaluation of monoisoamyl 2, 3-dimercaptosuccinic acid (MiADMSA)-encapsulated polymeric nanoparticles as a detoxifying agent for arsenic poisoning.Materials & Methods: Polymeric nanoparticles entrapping the DMSA monoester, which can evade the reticulo-endothelial system and have a long circulation time in the blood, were prepared. Particle characterization was carried out by transmission electron microscopy and dynamic light scattering. An in vivo study was conducted to investigate the therapeutic efficacy of MiADMSA-encapsulated polymeric nanoparticles (nano-MiADMSA; 50 mg/kg orally for 5 days) and comparison drawn with bulk MiADMSA. Swiss albino mice exposed to sodium arsenite for 4 weeks were treated for 5 days to evaluate alterations in blood, brain, kidney and liver oxidative stress variables. The study also evaluated the histopathological changes in tissues and the chelating potential of the nanoformulation.Results: Our results show that nano-MiADMSA have a narrow size distribution in the 50-nm range. We observed an enhanced chelating potential of nano-MiADMSA compared with bulk MiADMSA as evident in the reversal of biochemical changes indicative of oxidative stress and efficient removal of arsenic from the blood and tissues. Histopathological changes and urinary 8-OHdG levels also prove better therapeutic efficacy of the novel formulation for arsenic toxicity.Conclusion: The results from our study show better therapeutic efficacy of nano-MiADMSA in removing arsenic burden from the brain and liver.